Targeted Nutritional and Behavioral Feeding Intervention for a Child with Autism Spectrum Disorder - Kelly Barnhill; Amanda Tami; Claire Schutte; Laura Hewitson; Melissa L. Olive (Case Reports in Psychiatry)
A variety of feeding issues and concerns, including food aversion, food selectivity, and complete food refusal, are not uncommon among children with autism spectrum disorder (ASD). Other underlying issues are often comorbid with the concerns for feeding and ASD. These may include food allergies, gastrointestinal issues, oral motor issues, and swallowing disorders. The refusal to consume particular foods coupled with the inability to tolerate, digest, and absorb these foods can compromise an individual’s overall nutrition status. Therefore, a child’s behavior toward food and feeding activities has great impact on dietary intake, nutritional status, and growth. This case report is the first to document combined medical, behavioral, and nutritional intervention for a toddler with ASD and comorbid feeding disorder.